ANALISIS KREATIVITAS SISWA DALAM PEMBELAJARAN EKONOMI - Selvilianawati; Sulistiyarini; Syamsuri (FKIP Unswagati, 2025)
The purpose of this study was to determine the Creativity of Class X IPA 2 SMAN 2 Sungai Raya in Economic Learning, namely in understanding the material and doing assignments. The research method in this study uses a qualitative approach. Qualitative research is a method used in natural object conditions, where the researcher is the key instrument in taking random data sources, triangulation techniques, qualitative data analysis and the results of research are more about meaning. the form of research used is a case study. The informants in this study were Subject Teachers and Class X IPA 2 Students at SMAN 2 Sungai Raya, namely 1 teacher and 18 students. Data collection techniques using direct interviews, observation and documentation. The results of this study indicate that when understanding the subject matter there are 9 students with a percentage of 50.00% who can fulfill the characteristics of creativity, namely Originality, Fluency, Flexibility, Elaboration, whereas when doing assignments there are 12 students with a percentage of 66.67% who are at level 3 which is very creative because they can fulfill the 3 components of creativity which consist of fluency, flexibility, and elaboration. Keywords: Student Creativity, Economic Learning,Class X IPA.